Information Technology Audit in Optimizing Resources and Utilization of Financial Information Systems - Anggraini, Fransisca Dyah; S, Sumartono; Rusman, Hedar (PT.KARYA GEMAH RIPAH, 2024)
The utilization of financial information systems in companies has become part of the application of information technology, but there are challenges in the complexity and risk of its implementation. This study uses a qualitative and quantitative approach with the information technology audit method and the COBIT 5 framework. The research objectives analyzed the Maturity Level in the EDM, APO, BAI, and DSS domains using the COBIT 5 framework. The results showed a GAP between Current Maturity and Expected Maturity in each domain. The EDM domain has an average Current Maturity of 3.80, at the Manage and Measurable level, with the highest GAP in IT utilization. The APO domain has an average Current Maturity of 4.00, also at the Manage and Measurable level, with the highest GAP in portfolio management and IT quality services. The BAI domain has an average Current Maturity of 3.96, at the Manage and Measurable level, with the highest GAP in managing IT service availability and capacity. The DSS domain has an average Current Maturity of 4.40, at the Manage and Measurable level, with the highest GAP in the implementation of IT operating procedures. The research conclusions highlight areas of improvement involving information system management, information system portfolio management, and the effectiveness of operating financial reporting information system utilization procedures to improve maturity levels and optimize the utilization of the company's financial information systems.